Agroforestry as a Policy Instrument for Enhancing Sustainability of Public Green Open Spaces: Integrating MSA-ISM - Anita Primasari Mongan; Widiatmaka Widiatmaka; Hadi Susilo Arifin; Bambang Pramudya Noorachmat (Green Publisher Indonesia, 2026)
Rapid urban expansion has intensified pressure on public green open spaces and reduced the ecological functions of urban landscapes. Urban agroforestry has increasingly been recognized as a relevant nature-based approach, as it reinforces ecological functions, enhances community well-being, and optimizes the multifunctionality of public green open spaces amid urbanization pressures. However, its sustainability and policy implications in limited urban public green spaces remain insufficiently explored. This study aims to develop evidence-based policy priorities for managing limited and spatially fragmented public green open spaces by integrating agroforestry as a core policy component through the combination of Multi-Aspect Sustainability Analysis (MSA) and Interpretive Structural Modeling (ISM). The method employed is a combination of Multi-Aspect Sustainability Analysis and Interpretive Structural Modeling to assess the sustainability of urban agroforestry systems. A sustainability index of 51.84% indicated a moderately sustainable condition, with strong performance in ecological, social, and infrastructure dimensions but weaker outcomes in economic and legal–institutional aspects. Key drivers included consumer dependence on agroforestry products, the availability of Standard Operating Procedures (SOPs) for urban agroforestry management, and the economic value of agroforestry products (vegetables, fruits, timber, honey, livestock). The findings highlight the necessity of integrated, adaptive, and evidence-based policies to ensure the long-term sustainability of urban agroforestry systems and enhance the quality of public green open spaces.